Development of a 2D Educational RPG on the 10th November Battle - Alif Wisam Desanta Fitrianto; Chrystia Aji Putra; Andreas Nugroho Sihananto (bit-Tech, 2025)
The advancement of digital technology provides opportunities to innovate learning methods, especially for subjects like history that are often considered less engaging. This study develops a 2D Adventure RPG educational game themed on the November 10 Battle, integrating branching narrative and lane tower defense minigames to enhance students’ historical understanding. This integration addresses a research gap, as few studies have combined branching narrative and lane tower defense in a historical educational RPG. The game allows players to make choices affecting the storyline while facing strategic challenges through interactive mechanics. The study employed a single-group pre-test–post-test design involving 23 students from SMP Negeri 6 Surabaya. Results showed a significant improvement in learning outcomes, with the average score increasing from 53.48 to 94.78 and standard deviation decreasing from 19.21 to 5.93. The Wilcoxon Signed Rank test yielded p = 0.000 (< 0.05), confirming statistical significance. User experience evaluation using GUESS-18 indicated positive responses (mean scores 3.78–4.02), with branching narrative (4.06) and lane tower defense (3.94) receiving favorable feedback. Validity tests confirmed all items were valid (r > 0.413; p < 0.05), and reliability was high (Cronbach’s Alpha = 0.867). However, the small sample size (23 students) may limit generalizability of the findings. These findings suggest the November 10th educational game effectively improves historical understanding, cognitive and affective engagement, learning motivation, and strategic thinking. The study highlights gamified learning as an engaging alternative for history education in the digital era.